Quantitative analysis of chemical constituents in medicinal plant coleus aromaticus extracts - Kumar N., Santhosh; Nusrath, Aliya; Ramadas, Dinesha (International Journal of Research in Medical Sciences, 2018)
Background: Indian medicinal plants have great potential towards curing many diseases. Medicinal plant Coleus aromaticus is known for its wide medical applications. The main objectives of the study undertaken were to analyze the phytochemicals and compare the concentration present in the dialyzed Coleus aromaticus protein extract with various solvents. Methods: Various extracts of the medicinal plant Coleus aromaticus leaves such as dialyzed Coleus aromaticus protein, hydro alcoholic extract, ethanol extract and chloroform extract were prepared and analyzed for various phytochemical concentrations such as Total phenols (Folin-Ciocalteu method), Flavonoids (Aluminum chloride method), total sugars (Dubois method) and Proteins (Bradford’s method). Standard graph for each component was plotted. Results: The protein concentration in dialyzed Coleus aromaticus protein extract is considerably higher (5.8μg/10μl) than hydro alcoholic extract (1.6μg/10μl), ethanol extract (5.2μg/10μl) and chloroform extract (2.8μg/10μl). The other phytochemicals like total phenol, flavonoids and total sugars were low in concentration in the dialyzed Coleus aromaticus protein extract compared to hydro alcoholic extract, ethanol extract and chloroform extract. Conclusions: In this study, the protein concentration in dialyzed Coleus aromaticus protein extract is considerably higher than the same in other solvent extracts. This is the basis for further studies to unfold the antioxidant activity of Coleus aromaticus protein in vitro.